Tofacitinib: a janus kinase inhibitor for rheumatoid arthritis. Issue 8 (August 2017) - Chaplin, Steve
Abstract : Tofacitinib (Xeljanz) is an oral janus kinase (JAK) inhibitor indicated for the second‐line treatment of moderate to severe active rheumatoid arthritis in adults. This article discusses its properties, efficacy and adverse effects.